Cerebral metastases in metastatic breast cancer: disease-specific risk factors and survival - Heitz, Florian; Rochon, Justine; Harter, P.; Lueck, H. -J.; Fisseler-Eckhoff, A.; Barinoff, J.; Traut, A.; Lorenz-Salehi, F.; Du Bois, A. (Annals of oncology, 2011)
Background - Survival of patients suffering from cerebral metastases (CM) is limited. Identification of patients with a high risk for CM is warranted to adjust follow-up care and to evaluate preventive strategies. - Patients and methods - Exploratory analysis of disease-specific parameter in patients with metastatic breast cancer (MBC) treated between 1998 and 2008 using cumulative incidences and Fine and Grays’ multivariable regression analyses. - Results - After a median follow-up of 4.0 years, 66 patients (10.5%) developed CM. The estimated probability for CM was 5%, 12% and 15% at 1, 5 and 10 years; in contrast, the probability of death without CM was 21%, 61% and 76%, respectively. A small tumor size, ER status, ductal histology, lung and lymph node metastases, human epidermal growth factor receptor 2 positive (HER2+) tumors, younger age and M0 were associated with CM in univariate analyses, the latter three being risk factors in the multivariable model. Survival was shortened in patient developing CM (24.0 months) compared with patients with no CM (33.6 months) in the course of MBC. - Conclusion - Young patients, primary with non-metastatic disease and HER2+ tumors, have a high risk to develop CM in MBC. Survival of patients developing CM in the course of MBC is impaired compared with patients without CM.
Gesehen am 04.10.2022